Hydroponic TOGA Garden and Digitalization of Information as Learning Resources for Pharmacy Students of Yapan Pasir Pengaraian Vocational School: Kebun TOGA Hidroponik dan Digitalisasi Informasi Sebagai Sumber Belajar Siswa Farmasi SMK Yapan Pasir Pengaraian - Dahlia; Al Muzafri; Brahmana*, Eti Meirina; Nita Septiani; Desfi Harianti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
TOGA is a type of medicinal plant of choice used for first aid. TOGA can be planted hydroponically to overcome limited land. TOGA that has been cultivated can be used as a learning resource for students by presenting digitized information in the form of a QR-Code. Counseling regarding TOGA, Hydroponic training and digitalization outreach aims to provide broader knowledge to pharmacy students regarding TOGA and procedures for growing TOGA hydroponically so that it can support classroom learning. Students can obtain information by scanning the QR-Code from each TOGA. Yappan Pasir Pengaraian Vocational School has limited vacant land, while the pharmacy department requires TOGA in the school to support learning activities that are listed in the pharmacy department syllabus. Meanwhile, the presence of TOGA in schools is very minimal, there are only a few plants planted in pots. Apart from that, there is no complete information regarding TOGA, so students have difficulty utilizing the plants around the school. Therefore, it is necessary to present a TOGA hydroponic garden and also be equipped with digitalization of information in an effort to make it easier for students to obtain information. The results of this training are additional knowledge regarding TOGA, how to plant TOGA hydroponically and how to access information via QR-Code.